2019
DOI: 10.1016/j.celrep.2019.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Recruitment to Noninvasive MRSA at the Stratum Corneum of Human Skin Mediates Transient Colonization

Abstract: Graphical Abstract Highlights d S. aureus transiently colonizes the outer stratum corneum of healthy human skin d Noninvasive MRSA causes local inflammation in the underlying skin layers d Neutrophil recruitment to the skin reduces bacterial numbers on the skin surface d Neutrophils mediate the transiency of MRSA colonization SUMMARY Staphylococcus aureus is a leading cause of skin and soft issue infection, but paradoxically, it also transiently, and often harmlessly, colonizes human skin.An obstacle to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
(52 reference statements)
2
18
0
1
Order By: Relevance
“…Several separate reports demonstrate that immunodeficient mice support the engraftment of human skin 26 , 27 . Adult human skin-derived from either medical wastes (elective plastic surgery) 28 , 29 or tissue culture-derived engineered skin (keratinocytes and fibroblasts) 24 engrafts successfully in immunodeficient mice. Allogeneic adult human-peripheral blood mononuclear cells (PBMCs) have been introduced into these models to mimic human immune cell-skin interactions with infectious agents 24 , 29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several separate reports demonstrate that immunodeficient mice support the engraftment of human skin 26 , 27 . Adult human skin-derived from either medical wastes (elective plastic surgery) 28 , 29 or tissue culture-derived engineered skin (keratinocytes and fibroblasts) 24 engrafts successfully in immunodeficient mice. Allogeneic adult human-peripheral blood mononuclear cells (PBMCs) have been introduced into these models to mimic human immune cell-skin interactions with infectious agents 24 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Adult human skin-derived from either medical wastes (elective plastic surgery) 28 , 29 or tissue culture-derived engineered skin (keratinocytes and fibroblasts) 24 engrafts successfully in immunodeficient mice. Allogeneic adult human-peripheral blood mononuclear cells (PBMCs) have been introduced into these models to mimic human immune cell-skin interactions with infectious agents 24 , 29 . Although these mouse models demonstrate successful engraftment and development of transplanted human skin and are amenable to the transplantation of allogeneic PBMCs, said platforms are not currently coupled with the engraftment of autologous lymphoid tissues that are critical for a de novo immune response.…”
Section: Introductionmentioning
confidence: 99%
“…By measuring significantly upregulated human IL8 expression in skin biopsies, they were able to show the reaction of the human skin towards S. aureus. Moreover, they demonstrated that human IL8 is able to recruit murine neutrophils, which contribute to controlling MRSA growth on the human skin [ 208 ]. In another study, van Dalen et al investigated the interaction of human langerin with S. aureus WTA.…”
Section: Implications Of Staphylococcal Host Adaptation For Murinementioning
confidence: 99%
“…For example, Soong et al (2015) demonstrated that toxin-deficient, agr-mutants of S. aureus are able to persist on the human skin by stimulating autophagy. In addition, epicutaneously swabbed S. aureus on human skin xenografts led to local production of IL-8, which induced neutrophil migration to the skin to promote bacterial clearance (Schulz et al, 2019). Studies involving human skin xenograft infections are not widely used and thus represent an exciting opportunity in the dermatology field to translate the immunologic findings from mouse skin infection models to human skin.…”
Section: Human Skin Xenograft Modelmentioning
confidence: 99%